Produção de mudas de barbatimão [Stryphnodendron adstringens (Mart.) Coville] em substrato contendo lodo de esgoto - Isabela Reis Queiroz (2014)
It is known that the production of seedlings is very important to favor the propagation of endangered species and with economic potential, and that the usage of sewage sludge as organic fertilizer in agriculture, is considered as the most promising alternative for this residue final disposal, due to its sustainability. In this context, this study aimed to evaluate the production of barbatimão seedlings using sewage sludge as a substrate component. The experimental design was completely randomized. The experiment consisted of six treatments, four replications and the experimental unit comprised of four seedlings. The treatments were composed of sewage sludge mixed with typical Cerrado soil (v: v); being 0: 100 the control treatment (T1); 2.5: 97.5 (T2); 5:95 (T3); 10:90 (T4); 15:85 (T5) and 20:80 (T6). Were evaluated: emergency, nutritional characteristics survival and quality of the plants, and chemical and physical characteristics of the substrate. The control (T1), and treatment (T2) and (T3) had the highest rates of emergency and survival, respectively. The concentration of 15% (T5) was the one that provided the greatest seedling growth, followed by 5% (T3) and 2.5% (T2). All treatment plants with 20% sludge (T6) died, and the ones cultivated in the treatment composed of 15% sludge and 85% of the Cerrado soil (T5), expressed foliar signs of intoxication. The addition of 2.5 and 5% of sewage sludge to the substrate showed the best results for quality seedlings. Regarding the chemical properties of the substrate, it was observed that the doses 10 and 15 and 20% of sludge increased micronutrient levels to levels toxic to plants. Regarding the chemical properties, the sludge favored water retention capacity of the substrates in all concentrations. We conclude that the usage of low concentrations of sewage sludge seems to be a promising alternative in the composition of substrates for barbatimão seedling production.